Rancang Bangun Sistem Informasi Penjadwalan Project Studi Kasus PT. Bodha Dharmajaya Aryadhana Berbasis Web - Permana, Kevin Williams; Ramos, Samuel; Bani, Alexius Ulan (Journal of Engineering, Technology and Computing (JETCom), 2024)
With the rapid growth of the information technology (IT) industry, companies face various challenges in managing projects efficiently. PT. Bodha Dharmaja Aryadhana (BDA), as an IT solution provider, encounters difficulties in project scheduling, mainly due to the continued reliance on Excel spreadsheets, which have several limitations. These include restricted accessibility, insufficient support for team collaboration, lack of automation features, and the risk of data loss. To address these issues, this research develops a web-based project scheduling information system. The research uses observation, interviews, and literature studies for data collection. System modeling is conducted using UML, while the application is developed with PHP and the Laravel framework, alongside a MySQL database. System testing is carried out using the black box method to ensure its functionality operates correctly. By implementing this web-based information system, PT. BDA is expected to optimize resource utilization, minimize the risk of project delays, and enhance transparency and communication, ultimately improving client satisfaction..